Does good governance intensify the impact of energy finance on globalization? Evidence from BRICS nations - Md. Mominur Rahman; Md. Golam Faruque; Md. Emran Hossain (Research in Globalization)
In the context of globalization, good governance and energy financing are essential for sustainable and inclusive economic growth, particularly in emerging countries, as both are necessary for optimizing globalization. Existing research investigated the governance-energy-environment nexus; however, insufficient focus has been directed on the good governance-energy finance-globalization nexus in the BRICS countries. Hence, this study investigates the impact of energy finance and governance on globalization in BRICS countries, focusing on how energy finance, both fossil fuel and renewable, influences global integration. It examines the direct effect of governance on globalization and explores the moderating role of governance in strengthening the relationship between energy finance and globalization. Using advanced econometric models, including fully modified ordinary least square, augmented mean group, common correlated effects mean group, dynamic ordinary least square, two-stage least square, and generalized methods of the moment, the study provides empirical evidence on the significance of energy finance in driving globalization, with fossil fuel energy finance showing a negative impact and renewable energy finance a positive one. The results highlight the crucial role of good governance in enhancing the effectiveness of energy finance, suggesting that stronger governance frameworks can maximize the benefits of energy investments for globalization. This study provides novel insights by examining the moderating impacts of governance quality on the links between energy financing and globalization underpinning institutional theory within the BRICS nations. The findings highlight the necessity of improving governance frameworks to facilitate sustainable energy investments and globalization in BRICS states and other comparable countries, as effective governance and energy finance are both critical issues in the globalization discourse.